O papel de compostos de baixa cristalinidade em atributos físicos de horizontes com o caráter coeso - Silva, Dimitri Matos (2016)
The cohesive character occurs in the Coastal Tablelands and is defined as a pedogenetic densification identified due to changes in the consistence, being very hard to extremely hard when is dry and friable to firm when moisted. It occurs in Latossolos Amarelos and Argissolos Amarelos e Acinzentados. This work intended to test the hypothesis that the cohesive character occurs due to the presence of low crystalline material, presenting temporary cementation only when is in the process of drying and returning to a friable condition when is moisted. The experimental design utilized was completely randomized in fatorial schema (3x5)+2, with four repetitions, being the main factor the extraction of low crystallinity compounds in the levels: SE (without the extraction of low cristallinity compounds and saturation with distilled water), CE (with the extraction of low cristallinity compounds and saturation with distilled water) and CERS (extraction of low cristallinity compounds and saturation in a solution with Silicon). The second factor corresponds to five soil horizons with cohesive character: P1, P2, P3, P4, P5.The adittional treatment TA: without extraction of low cristalline compounds associated to saturation of silicon solution (SiO2) in the horizon with no cohesive character P6.In the control treatment TC: without the extraction of low cristallinity compounds and saturation with destilled water was used the horizon with no cohesive character P6, summing 68 experimental unities.The variables analysed were: density, hydraulic conductivity and penetration resistance. All the variables studied differed to the treatment without extraction. It is possible to conclude that the low cristallinity compounds should be associated to the cohesive character.